a) 30−[4(x−2)+15]=330−[4(x−2)+15]=3
b) 120+2.(8x−17)=214120+2.(8x−17)=214
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(8x+56:14=60\)
\(\Rightarrow8x+4=60\)
\(\Rightarrow8x=56\)
\(\Rightarrow x=\dfrac{56}{8}\)
\(\Rightarrow x=7\)
b) Mình làm rồi nhé !
c) \(41-2^{x+1}=9\)
\(\Rightarrow2^{x+1}=41-9\)
\(\Rightarrow2^{x+1}=32\)
\(\Rightarrow2^{x+1}=2^5\)
\(\Rightarrow x+1=5\)
\(\Rightarrow x=4\)
d) \(3^{2x-4}-x^0=8\)
\(\Rightarrow3^{2x-4}-1=8\)
\(\Rightarrow3^{2x-4}=9\)
\(\Rightarrow3^{2x-4}=3^2\)
\(\Rightarrow2x-4=2\)
\(\Rightarrow2x=6\)
\(\Rightarrow x=3\)
g) \(65-4^{x+2}=2014^0\)
\(\Rightarrow65-4^{x+2}=1\)
\(\Rightarrow4^{x+2}=64\)
\(\Rightarrow4^{x+2}=4^3\)
\(\Rightarrow x+2=3\)
\(\Rightarrow x=1\)
i) \(120+2\left(4x-17\right)=214\)
\(\Rightarrow2\left(4x-17\right)=214-120\)
\(\Rightarrow2\left(4x-17\right)=94\)
\(\Rightarrow4x-17=47\)
\(\Rightarrow4x=47+17\)
\(\Rightarrow4x=64\)
\(\Rightarrow x=16\)
a: \(8x+56:14=60\)
=>8x+4=60
=>8x=60-4=56
=>x=56/8=7
b: \(5^{2x-3}-2\cdot5^2=5^2\cdot3\)
=>\(5^{2x-3}=5^2\cdot3+2\cdot5^2=5^3\)
=>2x-3=3
=>2x=6
=>x=3
c: \(41-2^{x+1}=9\)
=>\(2^{x+1}=41-9=32\)
=>x+1=5
=>x=4
d: \(3^{2x-4}-x^0=8\)
=>\(3^{2x-4}-1=8\)
=>\(3^{2x-4}=8+1=9\)
=>2x-4=2
=>2x=6
=>x=3
g: \(65-4^{x+2}=2014^0\)
=>\(65-4^{x+2}=1\)
=>\(4^{x+2}=65-1=64\)
=>x+2=3
=>x=1
i: 120+2(4x-17)=214
=>2(4x-17)=214-120=94
=>4x-17=94/2=47
=>4x=64
=>\(x=\dfrac{64}{4}=16\)
x đầu ở đa thức A là x^3 chăng?
a/ \(A=x^3-5x^2+8x-4\)
\(=\left(x^3-x^2\right)+\left(-4x^2+4\right)+\left(8x-8\right)\)
\(=x^2\left(x-1\right)-4\left(x-1\right)\left(x+1\right)+8\)
\(=\left(x-1\right)\left(x^2-4x-4\right)=\left(x-1\right)\left(x-2\right)^2\)
b/ \(B=\dfrac{x^5}{30}-\dfrac{x^3}{6}+\dfrac{2x}{15}\)
\(=\dfrac{x^5}{30}-\dfrac{5x^3}{30}+\dfrac{4x}{30}\)
\(=\dfrac{x\left(x^4-5x^2+4\right)}{30}\)
\(=\dfrac{x\left(x^4-x^2-4x^2+4\right)}{30}\)
\(=\dfrac{x\left(x+2\right)\left(x-1\right)\left(x+1\right)\left(x-2\right)}{30}\)
\(a,[\left(8.x-12\right):4].3^3.3=3^6.6\)
\(\left(8x-12\right):4=54\)
\(8x-12=216\)
\(8x=228\)
\(x=28,5\)
\(b,41-2^{x+1}=9\)
\(2^{x+1}=41-9\)
\(2^{x+1}=32\)
\(2^{x+1}=2^5\)
\(\Rightarrow x+1=5\)
\(\Rightarrow x=4\)
\(3^2x-4-x^0=8\)
9x-4-1=8
9x-5=8
9x=13
=>x=\(\frac{13}{9}\)
Ta có
\(A=x^3-5x^2+8x-4=x^3-x^2-4x^2+4x+4x-4=x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)\)\(=\left(x^2-4x+4\right)\left(x-1\right)=\left(x-2\right)^2\left(x-1\right)\)
`a, 30 - [4(x - 2)+15] = 3`
`=> 4(x-2) + 15 = 30 - 3`
`=> 4(x-2) + 15 = 27`
`=> 4(x-2) = 27 - 15`
`=> 4(x-2)=12`
`=>x-2=12:4`
`=>x-2=3`
`=>x=3+2`
`=>x=5`
Vậy: `x=5`
`b, 120 + 2 . (8x-17)=214`
`=> 2 . (8x-17)=214-120`
`=> 2 . (8x-17)=94`
`=> 8x - 17 = 94:2`
`=>8x-17=47`
`=>8x=47+17`
`=>8x=64`
`=>x=64:8`
`=>x=8`
Vậy: `x=8`
a) 30 - [4 . (x - 2) + 15] = 3
30 - [4x - 8 + 15] = 3
30 - [4x + 7] = 3
4x + 7 = 30 - 3
4x + 7 = 27
4x = 27 - 7
4x = 20
x = 20 : 4
x = 5
Vậy x = 5
b) 120 + 2 . (8x - 17) = 214
2 . (8x - 17) = 214 - 120
2 . (8x - 17) = 94
8x - 17 = 94 : 2
8x - 17 = 47
8x = 47 + 17
8x = 64
x = 64 : 8
x = 8
Vậy x = 8